The Analysis of Heat Transfer Coefficient in Freezing Process of Cryotop - Wang Haisong; Zhou Xinli; Li Weijie (Zhileng xuebao)
The Cryotop is an efficient vitrification method for cryopreservation of oocytes. It has been widely used owing to its simple operation and high freezing rates. Recently, its heat transfer performance is frequently studied by the way of numerical simulation. However, the range of heat transfer coefficient in the simulation is uncertain. Three kinds of Cryotop models with different board thickness were studied. The cooling rates of water droplets in freezing process of Cryotop were measured by ultra-fast measurement and calculated by numerical simulation. Comparing the results obtained by two methods, the range of the heat transfer coefficient which was needed in the numerical simulation of Cryotop was found. The result showed that the range of the heat transfer coefficient is 6000~8000 W/(m2.K).